A virtual slotframe technique for reliable multi-hop IEEE 802.15.4e time-slotted channel hopping network - Yuvin Ha; Sang-Hwa Chung (International Journal of Distributed Sensor Networks)
Time-slotted channel hopping is one of the medium access control modes defined in IEEE 802.15.4e. Although time-slotted channel hopping provides high reliability, it cannot be achieved automatically. A time-slotted channel hopping should be configured properly according to the dynamic changes in a network. When new devices participate in the network or the data traffic is increased, link allocation may not be possible due to the fixed slotframe length. The simplest way to acquire additional links is to change the length. However, the conventional method to change this length involves significant overhead and the possibility of link failures. In this article, we evaluate the performance of the conventional IEEE 802.15.4e method and analyze the problems that can occur when changing the slotframe length. To resolve these problems, we propose a virtual slotframe technique that forms a logical slotframe by connecting multiple slotframes. A slot scheduler will then perceive the virtual slotframe as merely a long slotframe. The devices can translate the schedules made for the longer slotframe into real links using the virtual slotframe technique. These features allow the time-slotted channel hopping network to allocate additional slots without reconfiguration. The simulation results show that the proposed technique is a maximum of 18 times and an average of 10 times faster than the conventional method.